Pengaruh Work Satisfaction Terhadap Organizational Commitment Dengan Work Engagement Sebagai Variabel Mediasi - Anisah Mahdiyani, Shinta; Wahyu Gunawan P, Andreas (Fakultas Ekonomi Universitas Gresik, 2023)
This study aims to examine the effect of Work Satisfaction on Organizational Commitment with Work Engagement as a mediating variable. The population in this study were credit marketing staff employees in the Jabodetabek area banking. The sampling technique used a census of 100 respondents. Data analysis used the variant-based structural model equation method with the partial least squares approach using the SmartPLS version 3.2.1 application. The results showed that Work Satisfaction had an effect on Work Engagement, Work Satisfaction had an effect on Organizational Commitment, Work Engagement had no effect on Organizational Commitment and Work Satisfaction had no effect on Organizational Commitment through the Work Engagement variable. The managerial implications of this research are first, to increase work satisfaction, employees should be placed according to the educational background, work experience, and competency of the worker. Second, to increase Organizational Commitment to banking employees, companies retain employees by providing career path certainty in the company. Third, to improve Work Engagement, ideas from employees for the betterment of the company can be considered so that employees feel involved in their organization